2018
DOI: 10.1016/j.rmed.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Baseline serum CXCL10 and IL-12 levels may predict severe asthmatics' responsiveness to omalizumab

Abstract: High baseline serum CXCL10 and IL-12 levels may be useful in predicting a good omalizumab response in severe asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…25 For instance, when data from patients only treated with omalizumab were considered in the Study of Omalizumab (Xolair) in Subjects with Moderate to Severe Persistent Asthma (EXTRA), no substantial difference in exacerbation frequency between the high and low EoS and FeNO subgroups were observed, suggesting that all patients can benefit from omalizumab treatment irrespective of biomarker status. 25 Literature has reported that other biomarkers, such as IgE, 35e37 periostin, 38 C-X-C motif chemokine 10, 39 and interleukin-12, 39 may also be of importance for patients treated with omalizumab.…”
Section: Discussionmentioning
confidence: 99%
“…25 For instance, when data from patients only treated with omalizumab were considered in the Study of Omalizumab (Xolair) in Subjects with Moderate to Severe Persistent Asthma (EXTRA), no substantial difference in exacerbation frequency between the high and low EoS and FeNO subgroups were observed, suggesting that all patients can benefit from omalizumab treatment irrespective of biomarker status. 25 Literature has reported that other biomarkers, such as IgE, 35e37 periostin, 38 C-X-C motif chemokine 10, 39 and interleukin-12, 39 may also be of importance for patients treated with omalizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical markers, including IgE levels, blood eosinophil count and exhaled nitric oxide (Fe NO ) [7], are often a predictor of response and an indicator to which specific biological should be administered; however, a more complete profile is necessary to increase accuracy. For example, for omalizumab, the first approved biological targeting IgE, it was recently shown that a high baseline level of serum CXCL10 and IL-12 is predictive of a response to the treatment in severe asthma [8]. This not only predicts which patient groups benefit the most but also highlights the existence of different endotypes in allergy and asthma and the need for a more personalized approach in treating them.…”
Section: Biologicals Targeting Th2-type Immune Responses: Successful Translation From Bench To Bedsidementioning
confidence: 99%
“…More recently, a humanized anti-IgE antibody, omalizumab, has been developed to prevent binding of circulating IgE to FcεRI and the downstream effects of cross-linking ( 218 , 219 ). Omalizumab is a common and preferred treatment for chronic urticaria ( 220 , 221 ) and shows efficacy for the treatment of asthma ( 218 , 219 ); however, like many drugs, there appear to be responders and non-responders ( 222 ). These drugs represent both progress toward suppressing mast cell function and shortcomings supporting further development.…”
Section: Therapeutics Targeting Mast Cellsmentioning
confidence: 99%